PENGARUH LAMA AERASI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SAWI (Brassica juncea L.) PADA HIDROPONIK DFT (Deep Flow Technique) - Diah Yulita Ningrum; Sugeng Triyono; Ahmad Tusi (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2014)
This study aims to determine the effect of duration of aeration on the growth and yield of mustard plants (Brassica juncea L.), nutrient solution and electricity consumptions.  The experiment was conducted in September and October 2013 at The Integrated Field Laboratory, and Land and Water Resources Engineering Laboratory, The Departement of Agricultural Engineering, The University of Lampung.  The experiment consisted of four treatments of aeration intervals including N24M0 (control), N15M30 (15 minute on-30 minute off), N15M60 (15 minute on- 60 minute off) and N15M90 (15 minute on- 90 minute off).  Each treatment was divided into 3 segments along the gutter, including R1 (segment near the aerator), R2 (middle segment chamfer) and R3 (section away from the aerator).  The results showed that the use of a nutrient solution circulating pump with a flow rate of 0.27 cm/s is sufficient for EC, DO, pH fairly uniform along the gutter.  Aeration with interval 15 minute on- 60 minute off turned out to produce the highest mustard crop (2,146 kg) with the lowest consumption of fertilizer and electricity by IDR 1753.00/kg. Keywords: Aeration, DFT, hydroponics, intermitten, mustard